Compatibility of the State Aid Recovery Order with the General Principles of EU Law - Rzotkiewicz, Marek (Polish Review of International and European Law, 2017)
According to the Article 16.1 of Regulation 2015/1589 the Commission shall not require recovery of the aid if this would be contrary to a general principle of EU law. The potential existence of such a contradiction can be then of un utmost significance to a Member State and aid beneficiaries. However, notwithstanding its significance, the notion of a general principle of EU law has not been defined in the EU legislation, has been derived from the case law of the Court of Justice. The current paper strives to analyze different sorts of general principles of the EU law and their impact on the recovery obligation, especially as such an obligation differs between particular principles. Some of those principles have no significance at all on the existence of the recovery order, while others can, and sometimes even should, bar the Commission from ordering a Member State to recover an aid.